The Stubenberg meteorite—An LL6 chondrite fragmental breccia recovered soon after precise prediction of the strewn field. (30th May 2017) - Bischoff, Addi; Barrat, Jean‐Alix; Bauer, Kerstin; Burkhardt, Christoph; Busemann, Henner; Ebert, Samuel; Gonsior, Michael; Hakenmüller, Janina; Haloda, Jakub; Harries, Dennis; Heinlein, Dieter; Hiesinger, Harald; et al.
Abstract: On March 6, 2016 at 21:36:51 UT, extended areas of Upper Austria, Bavaria (Germany) and the southwestern part of the Czech Republic were illuminated by a very bright bolide. This bolide was recorded by instruments in the Czech part of the European Fireball Network and it enabled complex and precise description of this event including prediction of the impact area. So far six meteorites totaling 1473 g have been found in the predicted area. The first pieces were recovered on March 12, 2016 on a field close to the village of Stubenberg (Bavaria). Stubenberg is a weakly shocked (S3) fragmental breccia consisting of abundant highly recrystallized rock fragments embedded in a clastic matrix. The texture, the large grain size of plagioclase, and the homogeneous compositions of olivine (Fa31.4 ) and pyroxene (Fs25.4 ) clearly indicate that Stubenberg is an LL6 chondrite breccia. This is consistent with the data on O, Ti, and Cr isotopes. Stubenberg does not contain solar wind‐implanted noble gases. Data on the bulk chemistry, IR spectroscopy, cosmogenic nuclides, and organic components also indicate similarities to other metamorphosed LL chondrites. Noble gas studies reveal that the meteorite has a cosmic ray exposure (CRE) age of 36 ± 3 Ma and that most of the cosmogenic gases were produced in a meteoroid with a radius of at least 35 cm. This is larger than the size of the meteoroid which entered the Earth's atmosphere, which is constrained to <20 cm from short‐lived radionuclide data. In combination, this might suggest a complex exposure history for Stubenberg.